Weak neck problem in Musa sp. cv. rastali populations in relation to magnesium, boron and silicon availability - Putra, Eka Tarwaca Susila (2011)
Weak neck is the most significant physiological damage in Musa sp. cv. Rastali accessions. It has the ability to reduce fruit quality and selling value. A holistic approach is needed to solve the weak neck problem. The objectives of the research were: (1) to determine the genetic diversity of the Rastali population based on morphological and molecular markers, (2) to identify the specific allele that is associated with weak neck in the Rastali populations in comparison to other cultivars, and (3) to elucidate the relationship between fertilizer recommendation containing Mg, B and Si and the weak neck problem of the Rastali population. A total of 78 accessions of Rastali (74 accessions of Rastali from Peninsular Malaysia and 4 accessions from Central Java, Indonesia), and six different cultivars with no occurrence of weak neck were selected for comparison. Out of these, only 29 accessions were able to be morphologically characterized because many of them were without reproductive organ. A total of eight qualitative reproductive descriptors were used in this experiment. These 78 accessions were used for the molecular study. Genomic DNA were extracted from leaf samples using GeneAll® Plant DNA extraction kit and quantified using a spectrophotometer. Polymerase chain reaction (PCR) was performed in a total volume of 15μL. A total of 10 SSR primer pairs were used in this study. Meanwhile, forward primers were labelled with FAM fluorescent label. The detection of the DNA fragments was made on ABI Prism® 310 automated sequencer and the allele sizes were also obtained. The field experiment was done at Universiti Putra Malaysia under field conditions arranged in split-split plot design with five blocks. The main factor was NPK fertilizer which was recommended by Department of Agriculture Malaysia (DOA) and United Plantation Berhad (UPB). The sub-factors were applications and nonapplication (as control) of kieserite (Magnesium), boric acid (Boron) and sodium silicate (Silicon). The sub-sub factors were the Musa sp. cv. Rastali accessions,consisting of four groups, which were chosen for their different morphological characters. In particular, the Musa sp. cv. Berangan accession was selected as the control treatment. The findings showed that there is genetic diversity among Rastali accessions. Two male reproductive morphological descriptors (namely, male neuter flower along the rachis and male bud shape) were found to be the most important morphological characters which have caused the variation among the Rastali accessions. Existence of variations among Rastali was further supported by genetic analysis using 10 SSR markers. The SSRs markers were able to separate the accessions of Rastali. A significant 39% of genetic diversity was found among 78 accessions of Rastali. Out of the 78 Rastali accessions, eight were excluded from the main cluster, and showed higher heterogeneity compared to those in the main group (the coefficients of similarity ranging from 0.13 to 0.24). In the selection of the overall allele at each Rastali accession, one allele with the size of 238 bp, was found to be always present in all the accessions of Rastali, but was absent in the other six cultivars. This allele was located at locus A-25 and was considered the most common allele. Meanwhile, the allele which was located on locus A-13 and with the size of 277bp was only found in the other six cultivars but absent in all the Rastali accessions. The findings also showed that combined application of magnesium, boron and silicon could improve the Mg, B and Si contents in the leaves and fruit of the Rastali accessions and Berangan, in combination with the NPK fertilizer doses from DOA or UPB. These conditions increased the stomatal length and width and physiological activities of the Rastali accessions and Berangan at low level of NPK fertilizer (UPB), in combination with Mg, B and Si applications. In particular, the fingers of the R08 (in combination with the NPK fertilizer doses from UPB) and R62 (in combination with the NPK fertilizer doses from DOA) which had received Mg, B and Si were found to be lighter and smaller than those without any Mg, B and Si applications. Meanwhile, the bunches of the R08, R62 and Berangan which had received Mg, B and Si were found to be lighter and smaller than those without any Mg, B and Si applications, in combination with the NPK fertilizer doses from DOA. These characters have been shown to have the potential in reducing the intensity of the weak neck problem in the Rastali accessions, especially for the R08 and R62. Although the applications of magnesium, boron and silicon enhanced stomatal length and width and physiological activities of the Rastali accessions and Berangan at low level of NPK fertilizer (UPB), they decreased polygalacturonase (PG) and pectinmethylesterase (PME) activities in the Rastali accessions, except the PG on Day 4 after harvesting for the R08 and R62. Nevertheless, the PG and PME activities in Rastali were still higher compared to those of Berangan. The applications of Mg, B and Si also increased the lignin and cellulose content in the fruit neck zone of the R34 (in combination with the NPK fertilizer doses from DOA) and R08 (in combination with the NPK fertilizer doses from UPB). The decline in the PG and PME activities, as well as the increase in the lignin and cellulose content in the R08 (in combination with the NPK fertilizer doses from UPB) and R34 (in combination with the NPK fertilizer doses from DOA) which had received Mg, B and Si were able to increase the relative thickness of the cell walls during fruit growth. Application of Mg, B and Si resulted in small-sized cell but relatively thicker cell wall. Meanwhile, the applications of Mg, B and Si decreased the ethylene activity in the R08 (in combination with the NPK fertilizer doses from DOA or UPB), R34 and R12 (in combination with the NPK fertilizer doses from UPB). The decrease in ethylene, PG and PME activities delayed the accumulation of soluble soilids content (SSC) in the R08 (in combination with the NPK fertilizer doses from DOA) and chlorophyll degradation in the R12, which had obtained Mg, B and Si. The slowing down of chlorophyll degradation and the lowering of SSC resulted in maintained finger firmness of the fruit at a high level. Thus, the fruit has been found to remain strong and hard, especially in the abscission layer,although it has been ripened. The R08 and R12 which had obtained Mg, B and Si were able to produce fruit with stronger abscission layer (higher firmness), in combination with the NPK fertilizer doses from DOA. The stronger abscission layer is not easy to crack and it is also not prone to weak neck. Therefore, the applications of Mg, B and Si in combination with the NPK fertilizer doses from DOA have the potential to reduce the weak neck intensity in the R08, although totally eliminating the weak neck problem as in Berangan has yet to be achieved. Based on the data, it can therefore be concluded that (1) Rastali cultivar has weak neck problem, (2) there are early indications that the 238bp and 277bp alleles have the possibilities to be associated with weak neck, and (3) the combined applications of Mg, B and Si was able to reduce the weak neck intensity from 80.00% to 24.33% in the Rastali accessions and Berangan, in combination with the NPK fertilizer doses from DOA.